Hi again Simon;
x-3/4=3/2x+1/2
x - 3/2x = 1/2 + 3/4
factor x
x ( 1 - 3/2 ) = 3/4
x (-1/2 ) = 5/4
x = (5/4) / (-1/2)
x = - 10/4
x = -5/2
Could you guess what my only reason is??? !!!
Good Luck.
2006-09-12 13:02:52
·
answer #1
·
answered by sweetie 5
·
0⤊
1⤋
x - 3/2 x = 1/2 + 3/4
-1/2 x = 5/4
x = 5/4 multiply by - 2
x = -5/2 = -2 1/2
2006-09-12 10:55:34
·
answer #2
·
answered by Anonymous
·
0⤊
1⤋
Multiply the who bunch by common denominator (4), gives you
4x - 3 = 6x + 2
subtract 4x, then 2
-5 = 2x
x = -2 1/2
2006-09-12 10:57:06
·
answer #3
·
answered by dutch_prof 4
·
0⤊
1⤋
-5/2
2006-09-12 10:56:35
·
answer #4
·
answered by GeysaVD 3
·
0⤊
1⤋
multiply everything by 4:
4x - 3 = 6x + 2
2x = -5
x = -5/2
2006-09-12 10:55:29
·
answer #5
·
answered by sasmallworld 6
·
1⤊
1⤋
x-5/4=3/2x
-5/4=5/2x
-5/4=10/4x
-5/4/10/4=x
5/4=x
2006-09-12 11:01:39
·
answer #6
·
answered by Anonymous
·
0⤊
1⤋
www.Quickmath.com will help you alot
2006-09-12 10:58:52
·
answer #7
·
answered by Matt 1
·
0⤊
1⤋
you can't
2006-09-12 10:58:24
·
answer #8
·
answered by RP 2
·
0⤊
2⤋